Pengaruh Rasio Keuangan Sebagai Indikator dalam Memprediksi Potensi Kebangkrutan Bank Umum yang Terdaftar di Bursa Efek Indonesia - Fasha Asyva; Kristianingsih Kristianingsih; Rosma Pakpahan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to provide empirical evidence that financial ratios include in the Risk Based Bank Rating component can be used to predict the potential for bankruptcy of commercial banks and to determine financial ratios that can be used as indicators in predicting bankruptcy of commercial banks. This study uses secondary data in the form of bank financial statements for 2015-2019 at commercial banks listed on the Indonesia Stock Exchange, with 12 banks selected as samples through the purposive sampling method. The analytical technique used is panel data regression analysis with a random effect model. The test results show that the financial ratios included in the Risk Based Bank Rating component can be used to predict the potential for bankruptcy of commercial banks. However, partially, only LFR and CAR can be used as indicators to detect potential bankruptcy of commercial banks. Meanwhile, NPL, BOPO,and ROA cannot be used as indicators to predict the potential for bankruptcy of commercial banks.